2013
DOI: 10.7314/apjcp.2013.14.12.7367
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Side Effects of Sorafenib Therapy for Advanced Hepatocellular Carcinoma: A Retrospective Study by the Anatolian Society of Medical Oncology

Abstract: Background: Inoperable and metastatic hepatocellular carcinoma (HCC) is associated with a poor prognosis and low chemotherapeutic efficiency. Sorafenib is an oral multi-kinase inhibitor exerting its effects via the RAF/ MEK/ERK pathway, vascular endothelial growth factor receptor (VEGFR) and platelet derived growth factor receptor beta (PDGFR-β) tyrosine kinases. Randomized studies have shown a significant contribution of sorafenib to life expectancy and quality of life of cancer patients. The aim of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…And a meta-analysis also showed that sorafenib exerted significant curative effects in hepatocellular carcinoma (Wang et al, 2013). However, variation in the proportion of discontinuation might suggest a disagreement or different estimate of the consequences and risks for sorafenib discontinuation (Berk et al, 2013). A program supported by the China Charity Federation donates sorafenib treatment after administration for 3 months if patients are believed to benefit from continuation, regardless of the presence of PD.…”
Section: Discussionmentioning
confidence: 99%
“…And a meta-analysis also showed that sorafenib exerted significant curative effects in hepatocellular carcinoma (Wang et al, 2013). However, variation in the proportion of discontinuation might suggest a disagreement or different estimate of the consequences and risks for sorafenib discontinuation (Berk et al, 2013). A program supported by the China Charity Federation donates sorafenib treatment after administration for 3 months if patients are believed to benefit from continuation, regardless of the presence of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Others such as c-Raf, b-Raf, c-Kit and Flt3 are also key members of critical pathways for cell proliferation, differentiation and apoptosis (Kemmer et al, 2004;Kindler et al, 2010;Maurer et al, 2011;Berk et al, 2013). Sorafenib may have anti-tumor activities through a dual mechanism, acting indirectly on the tumor angiogenesis via VEGFR/PDGFR pathways and directly on tumor growth by inhibition Raf/Kit/Flt3 signaling (Wilhelm et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a variety of cytotoxic and antiproliferative agents have been tested in Hepatocellular carcinoma (HCC) treatment, which are used alone, or in combination with other drugs or other treatment modalities (Zhu, 2006;Boulin et al, 2011;Berk et al, 2013). However, high doses of these drugs lead to severe toxicities, which have a negative effect on patients' survival (Berk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, high doses of these drugs lead to severe toxicities, which have a negative effect on patients' survival (Berk et al, 2013). The use of less toxic doses in combination with other anti-proliferative agents would be desirable (Lee et al, 2004;Abou-Alfa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%